Predicting 1‐Year Mortality in Older Hospitalized Patients: External Validation of the HOMR Model. Issue 7 (3rd May 2019) - Curtin, Denis; Dahly, Darren L.; van Smeden, Maarten; O'Donnell, Desmond P.; Doyle, David; Gallagher, Paul; O'Mahony, Denis
Abstract : OBJECTIVES: Accurate prognostic information can enable patients and physicians to make better healthcare decisions. The Hospital‐patient One‐year Mortality Risk (HOMR) model accurately predicted mortality risk (concordance [C] statistic = .92) in adult hospitalized patients in a recent study in North America. We evaluated the performance of the HOMR model in a population of older inpatients in a large teaching hospital in Ireland. DESIGN: Retrospective cohort study. SETTING: Acute hospital. PARTICIPANTS: Patients aged 65 years or older cared for by inpatient geriatric medicine services from January 1, 2013, to March 6, 2015 (n = 1654). After excluding those who died during the index hospitalization (n = 206) and those with missing data (n = 39), the analytical sample included 1409 patients. MEASUREMENTS: Administrative data and information abstracted from hospital discharge reports were used to determine covariate values for each patient. One‐year mortality was determined from the hospital information system, local registries, or by contacting the patient's general practitioner. The linear predictor for each patient was calculated, and performance of the model was evaluated in terms of its overall performance, discrimination, and calibration. Recalibrated and revised models were also estimated and evaluated. RESULTS: One‐year mortality rate after hospital discharge in this patient cohort was 18.6%. The unadjusted HOMR model had good discrimination (C statistic = .78; 95% confidence interval = .76‐.81) but was poorly calibrated and consistently overestimated mortality prediction. The model's performance was modestly improved by recalibration and revision (optimism corrected C statistic = .8). CONCLUSION: The superior discriminative performance of the HOMR model reported previously was substantially attenuated in its application to our cohort of older hospitalized patients, who represent a specific subset of the original derivation cohort. Updating methods improved its performance in our cohort, but further validation, refinement, and clinical impact studies are required before use in routine clinical practice. J Am Geriatr Soc 1‐6, 2019.